Energy requirements of male academy soccer players from the English Premier League - Hannon, M. P.; Parker, L. J. F.; Carney, D. J.; McKeown, J.; Speakman, J. R.; Hambly, C.; Drust, B.; Unnithan, V. B.; Close, G. L.; Morton, G. P. (Medicine & Science in Sports & Exercise, 2021)
Purpose: This study aimed to inform the energy requirements of highly trained adolescent soccer players. Total energy expenditure (TEE) was quantified in academy soccer players from the English Premier League (EPL). Methods: Twenty-four male adolescent soccer players from an EPL academy (under (U) 12/13 (U12/13), n = 8; U15, n = 8; U18, n = 8) were assessed for baseline maturity (maturity offset), body composition (dual-energy x-ray absorptiometry), and resting metabolic rate (indirect calorimetry). Subsequently, TEE, energy intake (EI) and physical loading patterns were assessed over a 14-d in-season period using doubly labeled water, the remote food photographic method, and global positioning system technology, respectively. Results: U18 players presented with greater resting metabolic rate (2236 ± 93 kcal/d) and TEE (3586 ± 487 kcal/d; range, 2542-5172 kcal/d) than did both U15 (2023 ± 162 and 3029 ± 262 kcal·d-1, respectively; TEE range, 2738-3726 kcal/d) and U12/13 players (1892 ± 211 and 2859 ± 265 kcal·d-1, respectively; TEE range, 2275-3903 kcal·d-1; all, P < 0.01), although no difference in TEE was apparent between the U12/13 and U15 age groups. Fat-free mass was significantly different between all comparisons in a hierarchal manner (U18: 57.2 ± 6.1 kg > U15: 42.9 ± 5.8 kg > U12/13: 31.1 ± 3.5 kg; all, P < 0.01). Within age groups, no differences were apparent between EI and TEE (U12/13: -29 ± 277 kcal·d-1, P = 0.78; U15: -134 ± 327 kcal/d, P = 0.28; U18: -243 ± 724 kcal·d-1, P = 0.37), whereas U18 players (3180 ± 279 kcal/d) reported higher EI than did both U15 (2821 ± 338 kcal/d; P = 0.05) and U12/13 players (2659 ± 187 kcal/d; P < 0.01). Conclusions: The TEE of male academy soccer players progressively increase as players progress through the academy age groups. In some individuals (evident in all age groups), TEE was greater than that previously observed in adult EPL soccer players.